Application of the nZEB methodology in the retrofitting of a typical Portuguese dwelling from the 60's. - Monteiro, Joaquim (2016)
Buildings and the whole built environment are in a key role when societies are mitigating climate change and adapting to its consequences. More than 50% of the existing residential buildings in EU-25 were built before 1970. Thus, these buildings are of significant importance in reducing energy consumption and CO2 emissions. The existence of more nearly zero energy buildings (nZEB) is a possible solution for this problem. This study aims to analyze the application of the nZEB methodology in the retrofitting of a typical Portuguese dwelling build in 1950. It was shown that the primary energy used can be reduced to a very low value (11,95 kWhep/m2.y) in comparison with the reference consumption (69,15 kWhep/m2.y), with the application of the best construction techniques together with the use of energy from on-site renewable sources.